Exploring and expanding the phenotype and genotype diversity in seven Chinese families with spondylo-epi-metaphyseal dysplasia - Lv, Shanshan; Zhao, Jiao; Liu, Li; Wang, Chun; Yue, Hua; Zhang, Hao; Li, Shanshan; Zhang, Zhenlin (Frontiers in Genetics, 2022)
Spondylo-epi-metaphyseal dysplasia (SEMD) is a heterogeneous group of disorders with differing modes of inheritance. The presenting symptom of SEMD is short stature (disproportion or proportion), usually combined with specific orthopedic symptoms. At present, more than 30 disease-causing genes can lead to SEMD, they have shown great and different genetic disorders overlapping clinical features, which complicated the diagnosis. Our aim is to expand the clinical and molecular phenotypes of Chinese patients with SEMD, and to explore their phenotype-genotype relations. Clinical data were collected, physical examinations were conducted, and X-ray radiography and genetic analyses were performed in 7 families involving 11 affected patients with SEMD. The clinical manifestations in 7 probands showed different degrees of short stature, all accompanied by special skeletal manifestations, 4 probands had extraosseous manifestations. X-rays of 7 probands showed that the common features were vertebral deformity, abnormal femoral head and neck, irregular shape of epiphysis, disorganization of metaphysis. Seven variants were identified in TRPV4 (c.694C>T, p.Arg232Cys), COL2A1 (c.654+1G>C; c.3266_3268del, p.Gly1089del), CCN6 (c.396T>G, p.Cys132Trp; c.721T>C, p.Cys241Arg), SBDS (c.258+2T>C) and ACAN (c.1508C>A, p.Thr503Lys) genes, including two novel variants and five previously reported variants. Two families showed intra family and inter family variability. In addition, we reported one case of SEMD with severe phenotype caused by ACAN gene mutation. Our study expands the phenotype and genetic spectrum of SEMD, and providing further evidence for the phenotype-genotype relations, which may help provide diagnostic ideas and improve procreative management of SEMD.